Scientific Method in Physical Education Learning: A Cross-Sectional Study - Nune Wire Panji Sakti; Rusdiana Yusuf; Adi Suriatno; Johan Irmansyah (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2021)
The physical education learning process through the scientific method emphasizes finding information about the basic techniques/skills taught and game rules to find solutions to every problem encountered. This study aims to determine the results of the implementation of the scientific method in learning physical education. The study design was a cross-sectional study. There were 386 students and three physical education teachers participants. The data collection procedure in this study used an assessment questionnaire for students and an interview protocol for physical education teachers. Two research instruments were used: student questionnaire sheets and teacher interview protocols. Student questionnaire data were analyzed using quantitative descriptive and physical education teacher interview data were analyzed using qualitative descriptive. The results of the assessment of the response of class students indicate that the implementation of the scientific method in physical education learning has been going very well. This is evidenced by the percentage value of the assessment of more than 75%, both in the initial, core, and final activity variables. This research has an impact on increasing the knowledge and competence of teachers related to scientific methods and improving the quality of physical education learning.